The quantity and quality of anti-PRP induced by the new Indonesian DTwP-HB-Hib vaccine compared to the Hib vaccine given with the DTwP-HB vaccine - Novilia Sjafri Bachtiar; Kusnandi Rusmil; Sunarjati Sudigdoadi; Hadyana Sukandar; Rini Mulia Sari; Cissy B. Kartasasmita (Indonesian Pediatric Society, 2017)
Background A phase II study of DTwP-HB-Hib vaccine compared to Hib (monovalent) vaccine given simultaneously with DTwP-HB vaccine has been done following the success of phase I study in infants, where the new DTwP-HB-Hib has excellent safety profiles and antibody responses in infants.Objective To evaluate the titer (quantity), avidity, and bactericidal capacity (quality of anti-polyribosylribitol phosphate/anti-PRP), of a new combined Bio Farma DTwP-HB-Hib (pentavalent) vaccine, compared to the Hib monovalent vaccine given simultaneously with the DTwP-HB vaccine (DTwP-HB+Hib).Methods The study was a prospective, randomized, open label, phase II trial. Subjects aged 6-11 weeks were allocated according to the randomization list. The pentavalent group received the DTwP-HB-Hib vaccine, while the monovalent group received the Hib monovalent and DTwP-HB vaccines separately. Immunizations were given in three doses with 28-day intervals. Blood specimens were taken before the first dose and 28 days after the last dose. We evaluated anti-PRP titers quantity (geometric mean antibody concentration/GMC) and seroprotection), followed by avidity and bactericidal (quality) testing. Titer and avidity of anti-PRP were tested using a modified version of the improved Phipps ELISA. Bactericidal capacity was evaluated using a Hib killing assay. Immune responses against other antigens in the vaccine were reported separately.Results One hundred five subjects in the pentavalent group and 106 subjects in the Hib monovalent group were tested for anti-PRP titers. Only 102 specimens for each group were available for bactericidal testing, due to insufficient volume for testing. Both vaccines induced similar anti-PRP titers, for GMC and seroprotection. Avidity increases were 82.9% and 76.4% in the pentavalent and Hib monovalent groups, respectively. Bactericidal activities were 94.1% and 89.2%, respectively. Both avidity and bactericidal activity were not significantly different between groups.Conclusion DTwP-HB-Hib vaccine induced anti-PRP quantity and quality comparable to those of the Hib monovalent vaccine given simultaneously with the DTwP-HB vaccine.